Heterologous expression of a β-d-glucosidase in Caldicellulosiruptor bescii has a surprisingly modest effect on the activity of the exoproteome and growth on crystalline cellulose. (1st December 2017) - Kim, Sun-Ki; Chung, Daehwan; Himmel, Michael E; Bomble, Yannick J; Westpheling, Janet
Abstract: Members of the genus Caldicellulosiruptor are the most thermophilic cellulolytic bacteria so far described and are capable of efficiently utilizing complex lignocellulosic biomass without conventional pretreatment. Previous studies have shown that accumulation of high concentrations of cellobiose and, to a lesser extent, cellotriose, inhibits cellulase activity both in vivo and in vitro and high concentrations of cellobiose are present in C. bescii fermentations after 90 h of incubation. For some cellulolytic microorganisms, β-d -glucosidase is essential for the efficient utilization of cellobiose as a carbon source and is an essential enzyme in commercial preparations for efficient deconstruction of plant biomass. In spite of its ability to grow efficiently on crystalline cellulose, no extracellular β-d -glucosidase or its GH1 catalytic domain could be identified in the C. bescii genome. To investigate whether the addition of a secreted β-d -glucosidase would improve growth and cellulose utilization by C. bescii, we cloned and expressed a thermostable β-d -glucosidase from Acidothermus cellulolyticus (Acel_0133) in C. bescii using the CelA signal sequence for protein export. The effect of this addition was modest, suggesting that β-d -glucosidase is not rate limiting for cellulose deconstruction and utilization by C. bescii.